IMPROVING THE EFFICIENCY OF NUMERICAL PROCESSING ALGORITHMS FOR BIOMEDICAL SIGNALS IN ARTIFICIAL INTELLIGENCE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Abstract: Artificial intelligence technologies make it possible to radically increase the effectiveness of digital processing of biomedical signals in the field of modern medicine. Biomedicine signals are complex and variable data that reflect the various physiological processes of the human body, and their precision analysis is important in further improving diagnostic, monitoring and treatment processes in medicine. Traditional digital signal processing methods often face limitations in the complete and efficient processing of these complex signals. Therefore, advanced artificial intelligence algorithms open up new opportunities in this area, which serves to increase the efficiency of algorithms for digital processing of biomedical signals.